Drought responsive gene expression regulatory divergence between upland and lowland ecotypes of a perennial C4 grass - Lovell, John T.; Schwartz, Scott; Lowry, David B.; Shakirov, Eugene V.; Bonnette, Jason E.; Weng, Xiaoyu; Wang, Mei; Johnson, Jenifer; Sreedasyam, Avinash; Plott, Christopher; Jenkins, Jerry; Schmutz, Jeremy; et al. (Genome Research, 2016)
Climatic adaptation is an example of a genotype-by-environment interaction (G×E) of fitness. Selection upon gene expression regulatory variation can contribute to adaptive phenotypic diversity; however, surprisingly few studies have examined how genome-wide patterns of gene expression G×E are manifested in response to environmental stress and other selective agents that cause climatic adaptation. Here, we characterize drought-responsive expression divergence between upland (drought-adapted) and lowland (mesic) ecotypes of the perennial C4 grass, Panicum hallii, in natural field conditions. Overall, we find that cis-regulatory elements contributed to gene expression divergence across 47% of genes, 7.2% of which exhibit drought-responsive G×E. While less well-represented, we observe 1294 genes (7.8%) with trans effects. Trans-by-environment interactions are weaker and much less common than cis G×E, occurring in only 0.7% of trans-regulated genes. Finally, gene expression heterosis is highly enriched in expression phenotypes with significant G×E. As such, modes of inheritance that drive heterosis, such as dominance or overdominance, may be common among G×E genes. Interestingly, motifs specific to drought-responsive transcription factors are highly enriched in the promoters of genes exhibiting G×E and trans regulation, indicating that expression G×E and heterosis may result from the evolution of transcription factors or their binding sites. P. hallii serves as the genomic model for its close relative and emerging biofuel crop, switchgrass (Panicum virgatum). Accordingly, the results here not only aid in the discovery of the genetic mechanisms that underlie local adaptation but also provide a foundation to improve switchgrass yield under water-limited conditions.